An Intervention to Reduce Hypoglycemia Fear in Parents of Young Kids with Type 1 Diabetes Through Video-Based Telemedicine (REDCHiP): Trial Design, Feasibility, and Acceptability - Marker, Arwen M. (Diabetes Technol Ther, 2020)
Background: Fear of hypoglycemia (FH) is common in parents of young children with type 1 diabetes (T1D) and problematically linked to maladaptive behaviors to avoid low blood glucose, parenting stress, and burnout. This study examined the feasibility and acceptability of a novel group-based telemedicine intervention to reduce FH in parents of young children with T1D. Materials and Methods: Forty-three families of a young child with T1D (1–6 years of age; diagnosed with T1D for at least 6 months) enrolled in the study and 36 completed the Reducing Emotional Distress for Childhood Hypoglycemia in Parents (REDCHiP) intervention. We assessed intervention feasibility with rates of attrition, intervention attendance, and fidelity to the treatment manual. We assessed acceptability with treatment satisfaction surveys and qualitative interviews (from a subset of completers; n = 10) about intervention acceptability, facilitators, and challenges. Results: Study attrition was 21%, including long-term follow-up (16% before or during the treatment phase). On average, parents attended 94% of intervention sessions and fidelity to the treatment manual was 89%. Intervention completers reported high satisfaction with the treatment groups (89% average satisfaction rating). Parent-reported positive influencers of the REDCHiP intervention were increased knowledge, fear awareness, coping strategies, confidence, behavioral parenting strategies, and support, whereas intervention challenges included feeling fearful or overwhelmed, family stress, lack of trust, and difficulty connecting with other group members. Conclusions: The REDCHiP intervention demonstrated initial feasibility and acceptability. Next steps include determining the intervention's impact on objective parent and child outcomes (e.g., glycemic control, parental FH, and parental stress/distress) as well as large-scale efficacy testing.